Internet of Things based Smart Parking System - Soosay Nathan, Shelena; Mohd Khairudin, Aida Nabilah; Saiful Bahri, Muhammad Najmi Afiq; Jaafar, Muhammad Alifuddin (Multidisciplinary Applied Research and Innovation, 2020)
A smart parking system is a parking area which is developed with various technologies to serve users better. Parking areas enhanced their security by collecting and verifying the vehicles plate when checking out. Wide options for smart payment are also available at most parking areas. Thus, these smart parking allows customers to optimize shopping time by helping them find a nearby parking spot, provide realtime information on parking space and provide smart payment services. This study aimed in developing Auto Gate Smart Parking System which applies the concept of Internet of Things. The methodology used in the development is Input Process Output model in steps which include analysis requirement, design and testing, and evaluation.  This system that uses an Auto Number Plate Recognizer (ANPR) through Raspberry Pi to detect the vehicle’s plate number and with the help of ultrasonic sensor, Raspberry Pi camera, database and an Arduino board. Testing was conducted by registering vehicle plate number into the database through Google Form and the system was tested with the registered plate number vehicle. It has shown that the system had effectively recognized the vehicle’s plate numbers which makes it easy for parking for small organizations to control their parking area. The system provides convenience to users as no direct interaction is needed for access.  Given the current situation in facing Covid-19, it is very important to have contactless systems. Therefore, this Auto Gate Smart Parking will be a great tool to be used in an authorized parking area